We are diverse but belonging to the same team: an empirical study on the relationship between diversity and identification - Venturini, Beatrice; Mosso, Cristina O.; Bellotto, Massimo (La camera blu. Rivista di studi di genere, 2015)
The present study aims to highlights the role of work group culture and gender diversity on work group functioning. Gender diversity is an aspect of organizational life and research on the effect of workgroup composition has yielded ambiguous results. The categorization elaboration model (van Knippenberg, De Dreu & Homan, 2004) addresses this issue and suggests examining factors influencing the relationship between work group diversity and work group functioning. The present study proposes that the group gender diversity affects group identification and that this effect is contingent on group norms. 18 work groups in an information technology enterprise were involved. Results confirmed the hypothesis. Theoretical and practical implications are discussed.